UNDERSTANDING OF CONSUMER DEMAND AND THE ABILITY TO COMPETE IN THE CARIBBEAN (LATIN AMERICA). - Rauzi Ramazalena; Frengki Putra Ramansyah; Muhammad Multazam; Rico Nur Ilham; Irada Sinta (RADJA PUBLIKA, 2024)
The Latin American region is a region that has Abundant natural resources Owned natural resources can strengthen the potential Economy, especially in terms of increasing cooperation with Indonesia which can be pursued through incentive and well-planned economic diplomacy.